How external and internal resources influence user action: the case of infusion devices. Issue 4 (November 2016) - Iacovides, Ioanna; Blandford, Ann; Cox, Anna; Back, Jonathan
Abstract Human error can have potentially devastating consequences in contexts such as healthcare, but there is a rarely a simple dichotomy between errors and correct behaviour. Furthermore, there has been little consideration of how the activities of users (erroneous and otherwise) relate to the conceptual fit between user and device, despite the fact that healthcare technologies are becoming increasingly prevalent and complex. In this article, we present a study in which nurses' conceptions of infusion device practice were elicited to identify misfits. By focusing on key concepts that users work with when setting up infusions and the extent to which the system supports them, our analysis highlights how actions are influenced by the different resources available to users including: the device itself; supporting artefacts; the conceptual understanding of the user; and the community of practice the user is part of. The findings reveal the ways in which users are resourceful in their day-to-day activities and also suggest potential vulnerabilities within the wider system that could threaten patient safety. Our approach is able to make previously under-explored aspects of practice visible, thus enabling insight into how users act and why.